The effect of education types on knowledge level in natural disaster information transfer - Batu, Mikail; Oz, Mustafa; Karaaslan, İlknur Aydoğdu and Yanık, Akan and Kayacan, Şehriban and Dıvrak, Ebru (Frontiers in Communication, 2024)
This study explores the most effective educational methods for conveying information about natural disasters in large institutions like universities. Focusing on a sample of 405 students from Ege University (Turkey), it examines whether knowledge levels about natural disasters vary based on demographic factors such as gender, faculty, and class year. The findings reveal significant differences in knowledge based on these demographics. The study also shows that disaster education enhances overall knowledge and reduces these demographic disparities. Additionally, it compares the effectiveness of different communication tools—face-to-face, brochures, and videos—demonstrating that face-to-face and video-based methods are more effective than brochures in delivering disaster-related information.